2016
DOI: 10.15171/ijoem.2016.806
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Patterns and Occupational Risk Factors of Human Brucellosis in Greece, 2004–2015

Abstract: Brucellosis incidence in specific occupational groups was much higher than in the general population. These results underline the importance of collecting information on occupation, both during the diagnostic process and in the surveillance system. Besides efforts to control brucellosis in animals, organized prevention efforts are needed within an occupational health framework, especially for the most vulnerable workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 7 publications
2
27
1
1
Order By: Relevance
“…Our finding of almost two-thirds of cases reporting a history of consumption of raw unpasteurized milk is consistent with findings of studies conducted in Greece and Iran reporting 77.1% and 100% frequency of raw unpasteurized milk consumption, respectively [22,23]. However, in contrast to other studies, we did not reveal any association between the consumption of raw unpasteurized milk, undercooked meat or exposure to animal carriers and disease form [24,25].…”
Section: Discussionsupporting
confidence: 89%
“…Our finding of almost two-thirds of cases reporting a history of consumption of raw unpasteurized milk is consistent with findings of studies conducted in Greece and Iran reporting 77.1% and 100% frequency of raw unpasteurized milk consumption, respectively [22,23]. However, in contrast to other studies, we did not reveal any association between the consumption of raw unpasteurized milk, undercooked meat or exposure to animal carriers and disease form [24,25].…”
Section: Discussionsupporting
confidence: 89%
“…16 The high incidence of human brucellosis in Huludao is likely to be associated with the close contact with domestic animals, especially feeding and grazing with sheep or goat, which are supported by some other studies in China, 18,21 but against some studies in other countries which reported that ingestion of raw and unpasteurized dairy products was the main risk factor. [22][23][24] In 2016, the options "wearing masks" and "wearing gloves" were added into the case questionnaire, which could provide more detailed distribution information about the adoption of self-protective measures; while for the option "eating undercooked meat or consuming unpasteurized/raw dairy products" that was also added in the new version of the questionnaire, only 2.5% patients confessed this in the study population, which is different from that in some other studies (88.0%, 77.1% and 74.0%, respectively). [22][23][24] The options "drinking water from same well with livestock" and "keeping young lambs indoors" were removed, however, drinking water from same well with livestock is still a risk factor in Huludao (86.6%, n=477), and this risk factor was rarely analyzed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In 2016, the options "wearing masks" and "wearing gloves" were added into the case questionnaire, which could provide more detailed distribution information about the adoption of self-protective measures; while for the option "eating undercooked meat or consuming unpasteurized/raw dairy products" that was also added in the new version of the questionnaire, only 2.5% patients confessed this in the study population, which is different from that in some other studies (88.0%, 77.1% and 74.0%, respectively). [22][23][24] The options "drinking water from same well with livestock" and "keeping young lambs indoors" were removed, however, drinking water from same well with livestock is still a risk factor in Huludao (86.6%, n=477), and this risk factor was rarely analyzed in previous studies. All these results suggest that concentrating on the animal brucellosis is of great significance in order to prevent and control the human brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rate of Brucella in specific occupations and endemic regions was much higher than in the general population. There were occupations with high incidence rate of Brucella; butchers and abattoir workers (12.7), laboratory personnel (3.1) and veterinarians (53.2) (Lytras et al, 2016). Incidence rates in Saudi Arabia (214.4), Turkey (262.2), and Syria (1603.4), had been reported (Pappas et al, 2006;WHO, 1997).…”
Section: Introductionmentioning
confidence: 99%